Potato dormancy - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Simple techniques to interrupt the dormancy period of seed potatoes have been developed by the International Potato Centre for use in tropical countries. In Rwanda, the tubers are buried for two weeks after the harvest and planted four weeks later....